Family Minds: A randomized controlled trial of a group intervention to improve foster parents' reflective functioning. (15th August 2022) - Adkins, Tina; Reisz, Samantha; Hasdemir, Dilara; Fonagy, Peter
Abstract: Family Minds is a brief group psychoeducational parenting intervention designed to increase the reflective functioning (RF) and mentalization skills of foster parents. RF is important for foster parents who have to build relationships with children whose adverse experiences increase their risk for psychosocial challenges. A randomized controlled trial (RCT) for Family Minds was conducted in Texas with 89 foster parents. The main aims of this study were to examine whether the intervention could significantly increase the RF/mentalization skills of the foster parents and decrease their parenting stress. After 6 weeks, compared with the control group, intervention foster parents improved their RF via a lowering of pre-mentalizing and also significantly decreased parenting stress related to parent–child dysfunctional interactions. Other measures of RF and parenting stress showed no significant differences between groups. Foster child behavior was not significantly different between groups, although data at 6 months showed a possible lowering of internalizing symptoms for children of intervention parents. This RCT provides some encouraging evidence that Family Minds may increase RF in foster parents, improve parental sensitivity and their ability to emotionally regulate, decrease parenting stress related to challenging interactions with their foster children, and possibly decrease children's internalizing behavior.